Critical appraisal of definitions and diagnostic criteria for sarcopenic obesity based on a systematic review - Donini, Lorenzo M.; Busetto, Luca; Bauer, Jürgen M.; Bischoff, Stephan C.; Boirie, Yves; Cederholm, Tommy; Cruz-Jentoft, Alfonso J.; Dicker, Dror; Frühbeck, Gema; Giustina, Andrea; Gonzalez, Maria Cristina; Han, Ho-Seong; et al. (Clinical nutrition, 2019)
Summary Background Sarcopenic obesity is a clinical and functional condition characterized by the coexistence of excess fat mass and sarcopenia. Currently, different definitions of sarcopenic obesity exist and its diagnostic criteria and cut-offs are not universally established. Therefore, the prevalence and sensitivity of this condition for any disease risk prediction is affected significantly. Aim This work was conducted under the auspices of the European Society for Clinical Nutrition and Metabolism (ESPEN) and the European Association for the Study of Obesity (EASO). An international expert panel performed a systematic review as an initial step to analyze and summarize the available scientific literature on the definitions and the diagnostic criteria for sarcopenic obesity proposed and/or applied in human studies to date. Methods The present systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The search was conducted in April 2018 in three databases (PubMed, Scopus, Web of Science). Human studies conducted in both sexes, irrespective of ethnicity, and published from 2007 to 2018 were included; cohorts of individuals with obesity and acute or chronic conditions and treatments reported to negatively influence skeletal muscle mass and function independently of obesity were excluded from final analyses. The quality of the studies was evaluated using the Newcastle-Ottawa Scale (NOS) adapted for cross sectional studies. Results The electronic search retrieved 2335 papers of which 75 met the eligibility criteria. A marked heterogeneity in definitions and approaches to diagnose sarcopenic obesity was observed. This was mainly due to differences in the definitions of obesity and sarcopenia, in the methodologies used to assess body composition and physical function, and in the reference values for the variables that have been used (different cut-offs, interquartile analysis, diverse statistical stratification methods). This variability may be attributable, at least in part, to the availability of the methodologies in the different settings, to the variability in specialties and backgrounds of the researcher, and to the different settings (general population, clinical settings, etc.) where studies were performed. Conclusion The results of the current work support the need for consensus proposals on: 1) definition of sarcopenic obesity; 2) diagnostic criteria both at the level of potential gold-standards and acceptable surrogates with wide clinical applicability, and with related cut-off values; 3) methodologies to be used in actions 1 and 2. First steps should be aimed at reaching consensus on plausible proposals that would need subsequent validation based on homogeneous studies and databases, possibly based on analyses of existing cohorts, to help define the prevalence of the condition, its clinical and functional relevance as well as most effective prevention and treatment strategies.